Visualization of water concentration distribution in human skin by ultra-multiplex coherent anti-Stokes Raman scattering (CARS) microscopy. (7th April 2021) - Kaneta, Daiki; Kimura, Masahiro; Leproux, Philippe; Couderc, Vincent; Goto, Makiko; Egawa, Mariko; Kano, Hideaki
Abstract: Ultra-multiplex coherent anti-Stokes Raman scattering (CARS) spectroscopic imaging was used to visualize the distribution of water concentration in human skin ex vivo. The CARS signal of the OH stretching vibrational mode of water was found to coexist with the signal of intercellular lipids such as ceramides, which were visualized by a sharp vibrational band at 2882 cm −1 . Depth-resolved CARS spectroscopic imaging of a skin sample revealed that ceramides were localized in the stratum corneum. These findings demonstrate the powerful potential of CARS spectroscopic imaging for probing pathological changes caused by anomalous water concentration distribution in human skin.